Manganês e flúor para o manejo da mancha aureolada do cafeeiro (Pseudonomas syringae pv. garcae) - Velloso, Jeanny Alice (2015)
In order to evaluate the effect of concentrations of manganese (Mn) and fluorine (F) for the management of bacterial blight in coffee, experiment was conducted initially in greenhouse and later under controlled conditions in growth chamber to evaluate the intensity of the disease and photosynthesis. The assay was conducted in the Department of Plant Pathology (DFP), at Lavras Federal University (UFLA). The susceptible cultivar Catuaí Vermelho IAC 99 was used. Treatments consisted of a combination of five Mn concentrations (0, 0.7, 1.4, 2.8, and 5.6 g L -1 ) and five F concentrations (0, 0.01875, 0.0375, 0.075 and 0.15 g L -1 ) in a factorial 5 x 5, totaling 25 treatments with four replications. The experimental design was a randomized block. There was a significant interaction between the concentrations of Mn and F to the area under disease progress curve of incidence (AUDPCI) and the area under disease progress curve of severity (AUDPCS). There was no influence of the interaction between the concentrations for Mn and F in the photosynthesis rate of the coffee seedlings, and no isolated effect for concentrations of F. The Mn concentrations significantly influenced photosynthesis, occurring decrease due to increase of the nutrient concentration.